Women’s Entrepreneurial Intentions: A Case From Madhesh Based On Skill - Mishra, Shila; Adhikari, Shukra Raj; Karki, Soni (New Perspective: Journal of Business and Economics, 2024)
This study investigates the impact of financial skills on women's entrepreneurial intentions in Madhesh Province. Specifically, it examines how cognitive skills, numerical ability, financial literacy, behavioral traits, risk tolerance, and entrepreneurial self-efficacy influence these intentions. A quantitative research design was employed using a survey with a sample of 385 female respondents, including students, job holders, and entrepreneurs. Data were collected through structured questionnaires distributed via mail and social media. The analysis utilized descriptive statistics, correlation, and multiple regression to assess the relationships between financial skills and entrepreneurial intentions. The analysis reveals that financial literacy and behavioral traits are significant predictors of women's entrepreneurial intentions in Madhesh Province. Conversely, cognitive skills, numerical ability, risk tolerance, and entrepreneurial self-efficacy do not show a statistically significant impact. The study confirms the validity of the regression model through collinearity statistics, ensuring robust results. The findings underscore the importance of financial literacy and behavioral traits in shaping women's entrepreneurial intentions. To promote female entrepreneurship, it is recommended to focus on enhancing financial education and developing key behavioral traits. The study contributes to the literature by highlighting region-specific factors affecting women’s entrepreneurial aspirations and suggests tailored interventions for fostering female-led ventures in Madhesh Province.